A QED description of relativistic Coulomb excitation in heavy ion collisions - Galetti, D; Kodama, T; Nemes, M.C (Elsevier, 1987)
A quantum electrodynamical treatment of Coulomb excitation in relativistic heavy ion collisions is presented. It is shown that a subtle interplay between quantum and relativistic kinematical effects induced by the nuclear recoil due to excitation generates a qualitatively different prediction (under certain kinematical conditions) from the corresponding prediction of conventional theories. The present formalism is applied to the clear fission problem and the results seem to solve the puzzle associated with this process for some time. © 1987.